KEY SKILLS REQUIRED TO COLLEGE PUBLIC ACCOUNTANT FOR MICRO AND SMALL ENTERPRISES OF PERU - Flores Konja, Adrian Alejandro (2013)
It is proposed to identify the skills required by the Peruvian SMEs to accounting professionals, and other factors related to the professional work force of Chartered Certified Accountants. To do this, based on professional competencies defined in the Educational Project of our School of Accounting at the University Dean of America, contained in Law 28 951 - Professionalization Act of CPA, and the proposal Tuning America as pattern comparison, there have been survey questionnaires applied to the top leaders of the unions representing SMEs - affiliated to the National Society of Industries Exporters Association, National Retail Federation, and the emerging empires Gamarra and Villa El Salvador - to identify what are the most needed skills for these to CPC, your personal profile, the fields of action within the enterprise, business functions, and its requirement (demand) relative to other professions, such as managers, engineers, economists and lawyers. In a brief analysis of the results, it has come to the conclusions that: competencies linked to the tax function are most needed at the level of micro and small enterprises, the accounting profession has insured current and potential demand in the field of MSEs, and remains one of the most requested among all professions by micro and small enterprises.